Regional aspects of the application of the «triple helix» model as a factor in the development of an innovative economy - E. A. Naumova; E. V. Sokolova (Путеводитель предпринимателя)
Business structures, scientific organizations and the state are the key subjects of national innovation systems, interacting, they form the so–called «triple helix». The subject of research in the article is the problem of the formation of the «triple helix» mechanism for the purposes of regional innovative development. In Europe, the mechanism of innovative development according to the «triple helix» model is the main one in regional development, and its components are equal partners, all three subjects interact with each other through the development of horizontal ties. In the Russian version, the mechanism has certain specifics. State funds remain the largest source of funding for Russian science. Basic scientific research is carried out by academic, not university structures. Universities do little to commercialize research results. It can be argued that in the Russian regions, the «triple helix» model as such is practically absent, however, there is some progress in its formation, there are successful examples. The authors systematize the main problems associated with the introduction of the «triple helix» mechanism and indicate directions for their solution.